The Lasting Effects of Early-Childhood Education on Promoting the Skills and Social Mobility of Disadvantaged African Americans and Their Children - García, Jorge Luis; Heckman, James J.; Ronda, Victor (Journal of Political Economy, 2023)
This paper demonstrates the long-term intragenerational and intergenerational benefits of the HighScope Perry Preschool Project, which targeted disadvantaged African-American children. We use newly collected data on the original participants through late middle age and on their children into their mid-twenties. We document long-lasting improvements in the original participants' skills, marriage stability, earnings, criminal behavior, and health. Beneficial program impacts through the childrearing years translate into better family environments for their children leading to intergenerational gains. Children of the original participants have higher levels of education and employment, lower levels of criminal activity, and better health than children of the controls.